Walkability variables: an empirical study in Rolândia - PR, Brazil - Leão, Ana Luiza Favarão (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2020)
The built environment is a key determinant of physically active lifestyles. Notwithstanding, as social reality and physical activity are connected (BAUMAN et al., 2012), relevant walkability constructs for larger cities and high-income countries may not be suited for Brazilian cities.  Therefore, the main objective of this research is to evaluate the relevance of individual walkability-built environment features in mid-size Brazilian cities. From the systematizing of spatial data and a subjective database from the Urban Mobility Plan (n=756) of a case study, eight different walkability-related urban form features were aggregated in 1000 meters street network buffers and tested. Walkability features were analyzed through a machine learning approach, utilizing the Random Forest Algorithm, with self-reported walking (meters walked per area unit). Results indicate that the most relevant walkability features were: Entropy (FI= 0.609), Integration at a 2000-meter radius (FI=0.136) and Residential Density (FI=0.060). These findings are of great implication to the operationalization of walkability in Brazilian cities, indicating that more traditional walkability models might not be ideal. Implications of these findings include informing local urban policies to adopt an evidence-based, contextually-tailored approach.